Background factors associated with academic motivation for attending medical school immediately after admission in Japan: A single‐center study - Takashi Watari; Nobuhiro Nagai; Kaori Kono; Kazumichi Onigata (Journal of General and Family Medicine, 2022)
Abstract Background To become a doctor with a high level of professionalism and ethical standards, it is important to have and maintain a high level of motivation right from medical school. However, studies in Japan have not quantitatively investigated the factors related to motivation immediately after enrollment. This study aimed to identify the demographic factors that influence the motivation of medical students immediately after admission. Methods A cross‐sectional single‐center study was conducted. First‐year medical students answered our questionnaire three weeks after the admission. The questionnaire comprised 16 demographic items and the 28‐item Academic Motivation Scale, which was used to quantify motivation. Results Our analysis showed that amotivation, representing low levels of self‐determinant motivation, was significantly higher in students whose parents were medical professionals and in students who did not talk about their problems than in those whose parents were not medical professionals and those who did talk about their problems. Intrinsic motivation, which indicates the level of self‐determinant motivation, was significantly lower in students who belonged to a sports club. Conclusions We suggest that having parents who are medical professionals may be associated with an individual's decreased motivation when entering medical school in Japan. Though this is a novel finding, further research is needed to analyze this relationship.